Neutrino masses and mass hierarchy: evidence for the normal hierarchy. Issue 8 (1st September 2022) - Jimenez, Raul; Pena-Garay, Carlos; Short, Kathleen; Simpson, Fergus; Verde, Licia
Abstract: The latest cosmological constraints on the sum of neutrino masses, in combination with the latest laboratory measurements on oscillations, provide "decisive" Bayesian evidence for the normal neutrino mass hierarchy. We show that this result holds across very different prior alternatives by exploring two extremes on the range of prior choices. In fact, while the specific numerical value for the Evidence depends on the choice of prior, the Bayesian odds remain greater than 140:1 across very different prior choices. For Majorana neutrinos this has important implications for the upper limit of the neutrino-less double beta decay half life and thus for the technology and resources needed for future double beta decay experiments.